2009
DOI: 10.1002/jhet.113
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antitumor activity of novel pyrazolylenaminone and bis(pyrazolyl)ketones via hydrazonoyl halides

Abstract: 3‐Acetyl‐4‐benzoyl‐1,5‐diphenylpyrazole reacts with DMF‐DMA to give the novel enaminone 2. The reaction of the latter with various hydrazonoyl halides afforded regioselectively the respective substituted (3‐pyrazolyl)(4‐pyrazolyl)ketones 4 in good over all yield. The preliminary screening for the antitumor activity of the synthesized compounds 2 and 4a, 4b, 4c, 4d, 4e, 4f, 4g against human breast cancer cell line (MCF‐7) revealed that both compounds 2 and 4b have high‐antitumor activity. SAR is discussed. J. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…3 Condensation of each of the pyrazoles 5a-e with N,N-dimethylformamidedimethylacetal (DMF-DMA) yielded the respective enaminones 6a-e in 75-85% yield (Scheme 1). The structures of the enaminones 6a-e were confirmed by their spectra (MS, IR and 1 H NMR (see Experimental).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Condensation of each of the pyrazoles 5a-e with N,N-dimethylformamidedimethylacetal (DMF-DMA) yielded the respective enaminones 6a-e in 75-85% yield (Scheme 1). The structures of the enaminones 6a-e were confirmed by their spectra (MS, IR and 1 H NMR (see Experimental).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported that heterocyclic enaminones of types 1 and 2 (Scheme 1) each exhibited an unexpected activity against the human breast cancer cell line MCF-7. [1][2][3] Also, several reports indicate that cyclic enaminones of type 3a-d (Scheme 1) proved to exhibit anticonvulsant properties and represent a new exciting series of compounds with efficacy in reducing seizures and hence are of great potential for the treatment of epilepsy. [4][5][6][7][8][9][10][11] In the light of these findings and in continuation of our recent work on the utility of enaminones for synthesis of hetaryl-pyrazoles, 1,2 it was thought interesting to synthesise new substituted enaminones 6 (Scheme 2) and explore their antitumor activity to shed some light upon structure activity relationships (SAR) and to study their reactions with some nitrogen and carbon nucleophiles.…”
mentioning
confidence: 99%
“…In this synthesis strategy, nitrile imine derivatives ( 278 ) were firstly synthesized from hydrazonoyl halides compounds ( 277 ). Then, the bispyrazole compounds ( 282 ) were obtained by the regioselective 1,3‐dipolar cyclo addition reaction [65] . (Scheme 38).…”
Section: Formation Of Heterocycle Structures By Dmf‐dma Reactionsmentioning
confidence: 99%
“…Thiazole derivatives demonstrate significant biological properties such antifungal (abafungin), antimicrobial (sulfazole), anti‐inflammatory, anticancer, anticonvulsant, anti‐HIV, antihypertensive, anti‐gout (febuxostat), and antidiabetic activities (Figure ) . In addition, bis‐heterocyclic compounds as well as hybrid molecules, whose pharmacophores are integrated into a single molecule, were reported to display various biological activities, especially as fungicidal, antibacterial, tuberculostatic, anthelmintic, and antiamoebic . Because of the significant bioactivity and wide range of application of piperazine and thiazole derivatives as well as bis‐heterocyclic compounds, several publications reported concerning the synthesis of these derivatives .…”
Section: Introductionmentioning
confidence: 99%